Organic template-free synthesis of zeolite Y nanoparticle assemblies and their application in the catalysis of the Ritter reaction. Issue 13 (23rd January 2017) - Tang, Ting; Zhang, Lei; Dong, Hai; Fang, Zhongxue; Fu, Wenqian; Yu, Quanyong; Tang, Tiandi
Abstract : Zeolite Y nanoparticle assemblies with mesoporous structure has good catalytic performance in the Ritter reaction. Abstract : Zeolite Y nanoparticle assemblies (Y-NA) with a mesoporous structure were directly synthesized at 75 °C for 16 h without adding any organic templates. The changes in structure, morphology and textural parameters of the materials obtained after different crystallization times were investigated via powder X-ray diffraction (XRD), infrared spectroscopy (IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and N2 -sorption. The results show that Y-NA had a micro–mesoporous structure composed of highly crystalline particle assemblies with sizes of 400–900 nm. The H-form Y-NA (HY-NA) is strongly acidic, and exhibits a good catalytic performance in the Ritter reaction, as compared with the H-form microporous zeolite Y and mesoporous zeolite ZSM-5.